"Alive" or "not dead": The contribution of descriptors to attribute-framing bias. Issue 12 (December 2019) - Kreiner, Hamutal; Gamliel, Eyal
Attribute-framing bias (AFB) refers to bias in evaluating positively framed objects more favourably than the same objects framed negatively. In most AFB studies, framing is manipulated by contrasting the positive and negative outcomes, using the corresponding positive (success) or negative (failure) labels as descriptors. This study examined the unique contributions of the outcomes of the scenario and the labels describing these outcomes by manipulating them orthogonally. In three experiments, framing scenarios were presented to participants with either positive outcomes rendered with positive (65% passed) or negative (65% didn't fail) descriptors, or negative outcomes rendered with positive (35% didn't pass) or negative (35% failed) descriptors. All experiments revealed a strong effect for the outcome with a weaker effect for the descriptor valence, suggesting that outcomes have a stronger influence on AFB than do descriptors. We discuss the results within a theoretical framework that maps the outcome effects onto attention mechanisms and descriptor effects onto association-activation mechanisms.